Formulation, development and evaluation of topical nanoemulgel of tolnaftate - Gadkari, P. N.; Patil, P. B.; Saudagar, R. B. (Journal of Drug Delivery and Therapeutics, 2019)
Nanoemulsion has been identified as a promising delivery system for various drugs including Biopharmaceuticals. Nanoemulsion is heterogeneous system composed of one immiscible liquid dispersed as droplets within another liquid. Aim of the present study was to investigate the nanoemulgel as transdermal delivery system for poorly water soluble drug, Tolnaftate in order to overcome the troubles associated with its oral delivery. Different nanoemulsion components (Oil, Surfactant and Cosurfactant) were selected on the basis of solubility and emulsification ability. High pressure Homogenization techninique were used for the preparation of Nanoemulsion. Carbopol 934 was added as gel matrix to convert nanoemulsion into nanoemulgel. Drug loaded Nanoemulgels were characterized for particle size, SEM, Viscosity, Spreadability, Diffusion study using egg membrane, Nanoemulgel containing 3 % Almond oil, 5.25 % Tween 80, Proplene glycol as Cosurfactant, 1 % drug, Water upto Quantity sufficient was concluded as optimized formulation (F1). Keywords: Antifungal, Nanoemulsion, Gelling agent, Tolnaftate